Antibacterial Activity of Total Extract, Petroleum Ether, Chloroform, Ethyl Acetate and Aqueous Fractions of Aerial Parts of Heliotropium bacciferum - N Rahimifard; E Bagheri; G Asgarpanah; B Kabiri Balajadeh; HR Yazdi (Institue of Medicinal Plants, ACECR, 2014)
Background: Heliotropium bacciferum is one of the plants belonging to the family Boraginaceae, which is Restricted distribution in the south of Iran. It is used for Hypotension, fever, stomach ulcers in traditional medicine. Objective: In this study, the antibacterial effects of extracts and fractions of chloroform, ethyl acetate and aqueous, aerial parts of Heliotropium bacciferum Forssk was evaluated against five bacterial strains. Methodes: The methanol extract were prepared using the percolation method. Fractions of chloroform, Petroleum ether, ethyl acetate, methanol and aqueous respectively by Liquid - Liquid fractionation of the total extract were prepared. The antibacterial activity against two Gram positive bacteria, three Gram negative bacterial using Minimum inhibitory concentration in microplate and well plate method. Results: Results showed that H. bacciferum extracts exhibited a significant activity against strains Staphylococcus aureus, Bacillus cereus,Pseudomonas aeruginosa, E.coli and Salmonella enteritidis. MIC and well plate is between 7.6-125 µg/ml. Conclusion: The results of this study indicate that extracts of the plant H.bacciferum has a antimicrobial effect against strains are listed And among the extracts, aqueous part is that most antibacterial effect of the other fraction and then methanolic extract has the greatest effect.